Raça e religião: uma análise piscossocial dos discursos acerca das religiões afro-brasileiras - Santos, Matheus Laureano Oliveira dos (2010)
The dynamics of racial relationships in Brazil is a complex phenomenon. To understand this, it is necessary to approach its historical, political, economical and cultural implications, once ideas and several practices in relation to the black were built along the years. Regarding to racial relationships of Brazil, an important characteristic is the prejudice in relation to several African cultural aspects, more precisely, in relation to Afro-Brazilian religions. They present sui generis characteristics, once the initial prohibition of the cults and the consequent syncretism built along the time, through several fights, a diversity of expressions and knowledge that occupy important social environments. In this manner, we present the hypothesis that the prejudice in relation to the Afro-Brazilian religions does not only exist by virtue of an inter-religious differentiation, but that there are involved racial factors. The main objective of this study, then, is to verify if this relationship exists and what categorical and discursive processes that are involved. To achieve it, three studies were accomplished. The sample of the first two studies was composed by 77 people who profess catholic, evangelical and spiritist religions, while for the third study, the sample counted on 4 religious leaders. The first study consists of the categorization in which the subjects classify the apprentices of the Afro-Brazilian, Catholic, evangelical and spiritist religions with adjectives proper to sympathizer and nor-sympathizer people, as well as, with adjectives to first world people and third world people. That first study is based on researches of Camino and Cols. (2001 and 2004). The second study is the lexical analysis with the aid of ALCESTE software, of the following question: what are the essential elements of the Catholic, evangelical, spiritist and Afro-Brazilian religions? In this study, the analyses were based on the answers to the Afro- Brazilian religions and among the other three. The third study is an analysis of the religious leaders' speech about Afro-Brazilian religions in a concrete situation. In the first study, the expected relationship was not found. We found, in the second study, the discursive repertoires and the lexicons in relation to the Afro-Brazilian religions are related to primitive, to inferior. In relation to Catholic, evangelical and spiritist religions, the words and the discursive repertoires are in the ambit of the intergroup differentiation. In the third study, it was found several racist speeches in relation to black and African culture as being inferior, distant and that this culture needs to learn with the white culture so that it can diminish prejudice. It can be concluded that there is a strong relationship between the prejudice with the Afro-Brazilian religions and the racial prejudice.